(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigates the relationship between sports participation and psychological well-being among male university students in Pakistan, with a focus on stress, emotional resilience, and self-esteem. Drawing on Bandura’s Social Cognitive Theory, the research employed a quantitative design using a structured questionnaire adapted from validated scales, including the Perceived Stress Scale, Connor-Davidson Resilience Scale, Rosenberg Self-Esteem Scale, and the Warwick-Edinburgh Mental Well-Being Scale. A sample of 223 students from the Department of Sociology, International Islamic University Islamabad, was determined through Taro Yamane’s formula, and 201 valid responses were collected through online surveys. Data were analyzed using SPSS 27, applying reliability, correlation, and regression techniques. Findings revealed statistically significant but weak positive effects of sports participation on reducing stress, enhancing resilience, and improving self-esteem, with very low explanatory power (R² = 0.003–0.004). While results confirm that sports engagement contributes to psychological well-being, the modest effect sizes suggest that additional sociocultural, academic, and personal factors play a stronger role. The study highlights the importance of integrating sports into broader university mental health strategies and calls for longitudinal, multi-theoretical approaches to better understand the complex interplay between physical activity and student well-being in Pakistan.